Using cultural hybridity as an analytic lens for missiological research - Lee, Peter T. (Missiology, 2022)
This article considers cultural hybridity as a concept that helps interpret complex social phenomena found in various intercultural contexts in missions. The concept of cultural hybridity is better used as an analytic tool rather than an object of analysis in order for it to have an interpretive power. Adopting cultural hybridity in missiological research requires focusing on its active, dynamic, and processual nature found in the verb form, “hybridization,” rather than a stationary concept depicted by the noun form, “hybridity.” When using cultural hybridity in empirical studies, the mission researcher needs to develop a framework using the concept by immersing in the prior and current scholarly discussions, analyze social processes at multiple levels, utilize the hybridity theory in conjunction with other relevant social theories, and close the gap between the theory and data by focusing on how things work rather than forcing meanings out of the data. These practices may aid missiologists in their empirical research and increase their understanding of challenging intercultural issues.